Multinational firms and sustainability in global supply chains: scope and boundaries of responsibility - Marano, Valentina; Wilhelm, Miriam; Kostova, Tatiana; Doh, Jonathan; Beugelsdijk, Sjoerd (Journal of International Business Studies, 2024)
Multinational corporations and their global suppliers are increasingly expected to employ sustainability practices throughout their supply chains. As such, the global scope of corporate sustainability – including the notion of ‘full-chain responsibility’ – is a concern for firms, governments, NGOs, and other stakeholders. We evaluate the state-of-the-art of sustainability research on multinational firms and global supply chains, bringing together insights from two literatures that have examined this topic: international business and supply chain management. The articles in the Special Issue advance the research frontier by highlighting both macro impacts of legal and societal pressures as well as micro-processes of bargaining power, managerial sensemaking, and transparency to inform the relationships between global firms and their suppliers. Collectively, the research included in this Special Issue reflects a notable shift in focus from the former (macro) to the latter (micro). We elaborate on the benefits of incorporating additional notions such as power, opportunism, and negotiation in global supply chain research against the background of cross-country variation in legal and societal pressures. This would allow a more in-depth understanding of the dynamic relationships between multinational corporations, their multi-tier supplier networks, and other stakeholders that jointly shape the sustainability agenda.